Pls helppDoes m^2-4 equal to (m-2)(m+2)?

and does m^2+4 equal to (m-2)(m+2) also then??when simplified


Step-by-step explanation:

The difference of two squares takes the form

(x^{2} -y^{2} ) =(x-y)(x+y)

(x^{2} +y^{2} ) =(x+y)(x+y)

(m^{2} -4)=(m^{2} -2^{2} )=(m-2)(m+2)\\\\(m^{2} +4)=(m^{2} +2^{2} )=(m+2)(m+2)

I hope you understand!

Rate answer
Wrong answer?

If your question is not fully disclosed, then try using the search on the site and find other answers on the subject Mathematics.

Find another answers

Load image